Аналіз ферорезонансних процесів в розподільчому пристрої підстанції високої напруги за допомогою методів нелінійної динаміки - Кузнецов, В.Г.; Тугай, І.Ю. (Технічна електродинаміка, 2012)
It is shown that the problem of finding the necessary conditions of ferroresonance processes in the high-voltage switchgear substation belongs to a class of nonlinear dynamics problems. A system of equations, which allows to study of ferroresonance schemes and to plot of the phase space and corresponding Poincare cross-section of the normal sinusoidal mode and different types of ferroresonance processes is obtained. To verify the possibility of atypical ferroresonance the equivalent circuit parameters variations of the high-voltage switchgear substation within wide limits are considered.